Smoking Prevalence, Patterns, and Cessation Among Adults in Hebei Province, Central China: Implications From China National Health Survey (CNHS) - Huijing He; Li Pan; Ze Cui; Jixin Sun; Chengdong Yu; Yajing Cao; Ye Wang; Guangliang Shan (Frontiers Media S.A., 2020)
As part of the China National Health Survey, the objective of this study was to explore the prevalence, patterns, and influencing factors of smoking, and understand reasons for smoking cessation among adults in Hebei Province, central China. Using a multi-stage stratified cluster sampling method, 6,552 adults (2,594 males) aged 20-80 were selected in 2017. Demographic, socioeconomic, and tobacco use information were collected by questionnaire interview. The prevalence of ever-smoking, current smoking, and ex-smoking was 28.94, 21.08, and 7.86%, respectively. Male participants had a much higher prevalence of ever-smoking and current smoking (67.39 and 48.77%) than females (3.74 and 2.93%). In male participants, the daily cigarette consumption was 16.61, and the mean age of smoking initiation was 20.95, decreasing with birth year (27.50 in people born before 1946 vs. 17.9 for those born after 1985, p for trend < 0.001). Over 40% of male ever-smokers initiated regular smoking before 20. Compared with never drinking, the ORs (95% CI) of ever-smoking for low, moderate, and high alcohol consumption in male participants were 1.44 (1.11-1.86), 2.80 (1.91-4.11), and 2.40 (1.72-3.33), respectively. Among 479 male ex-smokers, 50.94% stopped smoking because of illness and 49.06% by choice. Among male ex-smokers, hypertensive men were more likely to quit smoking than the normotensive individuals (OR: 1.48, 95% CI: 1.13-1.96). For CVD patients, this effect was estimated as 2.27 (95% CI: 1.56-3.30). This study revealed a high prevalence of ever-smoking, especially in men, in a representative population in central China. Health education focus on tobacco control could be integrated with alcohol consumption reduction to achieve additional benefit.